2008
DOI: 10.1210/en.2008-0274
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Neurexin, Neuroligin, and Their Cytoplasmic Binding Partners in the Pancreatic β-Cells and the Involvement of Neuroligin in Insulin Secretion

Abstract: The composition of the beta-cell exocytic machinery is very similar to that of neuronal synapses, and the developmental pathway of beta-cells and neurons substantially overlap. beta-Cells secrete gamma-aminobutyric acid and express proteins that, in the brain, are specific markers of inhibitory synapses. Recently, neuronal coculture experiments have identified three families of synaptic cell-surface molecules (neurexins, neuroligins, and SynCAM) that drive synapse formation in vitro and that control the differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
71
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(79 citation statements)
references
References 66 publications
7
71
1
Order By: Relevance
“…Thus, in neurons, SORCS1 interacts with the synaptic adhesion molecule neurexin and controls trafficking of glutamate receptors, a process critical for plasticity of the synapse 59 . Remarkably, neurexin-1α and its ligand neuroligin are also expressed in pancreatic β-cells where they interact with components of the SG docking machinery to modulate insulin secretion rates [60][61][62] . Consequently, loss of expression of neurexin-1α 62 or neuroligin-2 63 alters islet morphology, pancreatic insulin content, and insulin secretion in mice.…”
Section: Sorcs1 a Diabetes Risk Factor And Regulator Of Insulin Secrmentioning
confidence: 99%
“…Thus, in neurons, SORCS1 interacts with the synaptic adhesion molecule neurexin and controls trafficking of glutamate receptors, a process critical for plasticity of the synapse 59 . Remarkably, neurexin-1α and its ligand neuroligin are also expressed in pancreatic β-cells where they interact with components of the SG docking machinery to modulate insulin secretion rates [60][61][62] . Consequently, loss of expression of neurexin-1α 62 or neuroligin-2 63 alters islet morphology, pancreatic insulin content, and insulin secretion in mice.…”
Section: Sorcs1 a Diabetes Risk Factor And Regulator Of Insulin Secrmentioning
confidence: 99%
“…Previous studies have already focused on the expression pattern of Neuroligin genes in different species (from mammals to birds), but few data concerning the alternative splicing pattern variation are available (Philibert et al, 2000;Bolliger et al, 2001;Chih et al, 2006;Suckow et al, 2008).…”
Section: Neuroligin Gene Family In Zebrafish 695mentioning
confidence: 99%
“…Neuroligin 1 expression is mainly restricted to the CNS, while Neuroligins 2-4 present a broader expression pattern (Song et al, 1999;Philibert et al, 2000;Bolliger et al, 2001;Gilbert et al, 2001;Kang et al, 2004;Suckow et al, 2008). Some lines of evidence suggest that the expression of Neuroligins may differ between species.…”
Section: Introductionmentioning
confidence: 99%
“…We previously found that neuroligin-2 (NL-2), 3 which is specific to inhibitory (GABAergic) synapses, is expressed by pancreatic ␤ cells and that alterations in its level of expression affected insulin secretion by primary rat islet and INS-1 ␤ cells (11,14). Increased NL-2 expression caused increased insulin secretion, and decreased expression lowered insulin secretion (14).…”
mentioning
confidence: 99%
“…Increased NL-2 expression caused increased insulin secretion, and decreased expression lowered insulin secretion (14). In work done elsewhere (15), NL-2 was one of the most abundant transcripts identified in a systematic study of human tissue mRNAs that was carried out in order to identify highly expressed, human islet-specific membrane proteins.…”
mentioning
confidence: 99%